Cropping of winter hydroponic forage in the cerrado pantanal ecotonon (Research, Society and Development, 2020)
Hydroponic forage is an alternative to feed the animal in times of drought quickly. Thus, the objective of this work was to evaluate the development of hydroponic forage of corn and millet irrigated with mineral and organic solutions during the winter season in the Cerrado-Pantanal ecotone, seeking to determine the species and the most suitable solution for the region at that time. The experimental design was in randomized blocks, in a split plot scheme. The plots were the solutions (mineral and organic) and the subplots were the populations of corn, millet and black mucuna and their respective proportions, totaling 12 treatments, with four replications. At harvest, the production of green and dry matter production was carried out and a bromatological analysis of the aerial part and substrate was carried out, determining crude protein, neutral detergent fiber, acid detergent fiber and mineral matter. The chemical evaluation of the organic solution was carried out in a fertigation analysis laboratory. Corn forage under mineral solution irrigation obtained better crude protein contents. The substrate that obtained the highest crude protein and the lowest fiber content was in the subplot with 100% millet for both solutions.